AN APPRAISAL OF THE AVAILABILITY AND USE OF INSTRUCTIONAL MATERIALS IN TEACHING MODERN AND NIGERIAN LANGUAGES (ENGLISH, IGBO AND YORUBA) IN LAGOS STATE JUNIOR SECONDARY SCHOOLS - Odewumi, Joy O. ,; Anyanwu Ngozi L. , Dom; Akanmu S. , Dayo (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2023)
This study looked at the appraisal of the availability and utilization of instructional materials for teaching of English and Nigerian indigenous languages (Igbo, Hausa, and Yoruba) in Nigeria junior secondary schools. The Scope of the research is Lagos State Junior secondary schools. Three Educational districts were used for the Study. The method adopted for the study was descriptive Survey. Two research instruments, teacher’s Questionnaires and observation checklist schedule were used for data collection. The data collected were analyzed using descriptive and inferential statistics. Major findings of the study includes; inadequate instructional materials in teaching Nigerian and modern languages in Nigerian junior secondary schools, the available instructional materials were not adequately utilized as a result of inexperienced and ill-trained teachers. The study concluded that there would be appropriate use of instructional materials by modern and Nigerian languages teachers if the government and the stakeholders could provide fund for the needed materials, employ qualified teachers as well as encourage and sponsor on-the-job training of Modern and Nigerian languages teachers.